(untitled) (Texas Journal of Medical Science, 2022)
Obesity is not only a medical but also a social problem. Epidemiologists predict that by 2025, 40% of men and 50% of women will suffer from obesity. In women, obesity is accompanied by a high frequency of anovulation, menstrual irregularities, infertility, hyperplasia and endometrial polyposis associated with impaired production of sex hormones, as well as a high risk of endometrial, ovarian, and breast cancer.